Unusual and early onset IPEX syndrome: a case report - Dilek Doğruel; Fatih Gürbüz; İhsan Turan; Derya Ufuk Altıntaş; Mustafa Yılmaz; Bilgin Yüksel (The Turkish Journal of Pediatrics)
Immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome is a rare disorder that causes systemic autoimmunity resulting from a mutation of the forkhead box protein 3 gene (FOXP3). A 2-year-old boy, was referred to the hospital due to vomiting and fever when he was 21 days old. On physical examination the patient was severely dehydrated, and his laboratory test results showed hyperglycemia and metabolic acidosis. Upon the continuance of the hyperglycemia which caused the patient to receive permanent insulin treatment, the patient was diagnosed with neonatal diabetes mellitus. Here, we report a 2-year-old boy with early-onset IPEX syndrome due to a c.1040G > A (p.R347H) mutation in exon 11 of the FOXP3 gene. Although the patient had missense mutation in his FOXP3 gene, he did not have other immunodysregulation symptoms. IPEX syndrome should be kept in mind in all the cases of associated neonatal diabetes mellitus in male neonates or infants.